PERTIMBANGAN HAKIM DALAM MENJATUHKAN PIDANA PENJARA TERHADAP ANAK SEBAGAI PENYALAHGUNA NARKOTIKA DI PENGADILAN NEGERI KELAS I A PADANG - Fitra Oktoriny, Eko Ananda dan (Normative Jurnal Ilmiah Hukum, 2022)
Criminal law is a set of rules that regulates 3 (three) elements, namely rules regarding criminal acts, criminal and criminal liability, if a crime occurs. The Juvenile Criminal Justice System explains that the juvenile criminal justice system is the entire process of resolving cases of children in conflict with the law, from the investigation stage to the guidance stage after serving a crime. From the results of research conducted regarding judges' considerations in imposing imprisonment on children for narcotics abuse at the Class I A Padang District Court in Decision Number: 170/Pid.Sus/2019/PN Pdg, it was found that by means of juridical considerations and the demands of the public prosecutor, both considerations This proves that the defendant is guilty of abusing shabu with the threat of punishment in Article 127 paragraph (1) letter a of Law Number 35 of 2009 concerning Narcotics jo. Article 55 paragraph (1) -1 of the Criminal Code and Law Number 8 of 1981 concerning the Criminal Procedure Code and other relevant laws and regulations. The application of criminal sanctions against children for narcotics abuse in the Padang District Court in decision number: 170/ Pid.Sus/2019/PN Pdg based on the judge's considerations, evidence, and witnesses, then LOIS VIGO FIRMAN PGL VIGO, then the Class 1 A Padang District Court decided that the defendant was proven guilty of narcotics abuse, the defendant's actions were as regulated and threatened with criminal in Article 114 paragraph (1) in conjunction with Article 132 paragraph (1) of Law Number 35 of 2009 concerning Narcotics, by imposing a prison sentence on the Defendant for 2 (two) years.